Urban Safety Nets and Activation in Mozambique - Zapatero, Eric L.; Majoka, Zaineb; Gallego-Ayala, Jordi; Zini, Michele D.; Beck, Peter; Ajwad, Mohamed Ihsan (World Bank, Washington, DC, 2017)
Thirty eight percent of the urban population in Mozambique is poor and the latest political and economic developments are likely to increase their vulnerability. Moreover, a large share of the urban population that is close to the poverty line and that could worsen their poverty status through small variations in income. In addition to the political and economic context, urbanization in Mozambique has been a steady process over the last years and this urbanization dynamic is likely to continue in the next coming years transforming Mozambique into one of the most urbanized countries in the region. This process will potentially exacerbate the unemployment situation in the urban settings, enhancing the vulnerability of the urban poor and specially the urban youth. Motivated by the increasing urban vulnerability, this report is one of the first attempts to review programs, practices and expenditure on safety nets and activation interventions in urban settings in Mozambique. In particular, the report aims at enhancing government knowledge and understanding about existing safety nets and activation programs in urban areas in Mozambique, assess their efficiency and effectiveness, and identify emerging lessons and challenges. The report aims at informing government on how to enhance the implementation of safety nets and activation programs is response to the increased vulnerability in urban areas. It does so by reviewing existing programs, published literature, and analyzing needs and target populations with household survey and administrative data and qualitative information collected through field surveys. The report focusses only on the core urban safety net and activation initiatives. The report is divided into three main chapters: Chapter 1 explains about the Profile of Mozambique’s poor urban population and urban safety nets beneficiaries; Chapter 2 describes Safety nets and activation programs assessment in urban Mozambique; and Chapter 3 concludes by Evaluating the readiness of Safety Nets and Activation initiatives in urban Mozambique.